THE STRATEGY OF READ ALOUD WITH QUALITY READING BOOKS ON LITERACY INTEREST AND SKILLS OF ELEMENTARY SCHOOL STUDENTS IN SIDOARJO REGENCY - Yetti Ulimawati; Adi Atmoko; Ratna Ekawati (LP2M IAIN Sultan Amai Gorontalo, 2026)
The low interest and reading skills in the early grades of elementary school indicate the need for an efficient learning strategy. One method proven to enhance literacy skills is the read-aloud activity. This study aims to explain the strategies implemented by teachers to improve reading literacy skills through read-aloud activities in the lower grades. The research method uses a qualitative descriptive approach with data collection techniques through interviews and observation. The findings of the study indicate that the read-aloud strategies applied by teachers, such as selecting engaging illustrated storybooks, using proper intonation and expression while reading, and post-reading reflection, canA increase students' interest and participation in reading activities. This activity also expands students' vocabulary and builds a good reading habit. This study emphasizes the significance of teacher training in expressive reading and the provision of quality reading books in elementary schools. Keywords: Reading Literacy, Read Aloud, Teacher Strategy.